2017
DOI: 10.31237/osf.io/qe9ck
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frontal Cortex Functioning in Infancy

Abstract: The functional status of the frontal cortex in infancy and early childhood is relatively poorly understood, and not much is known about the relationships between the few tasks developed to assess such functioning. The work presented in this thesis investigated these questions using an individual differences approach. Two cohorts of children were tested longitudinally on a set of tasks that have been associated with the frontal cortex in an attempt to establish whether these tasks share common functional mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 153 publications
(657 reference statements)
0
4
0
Order By: Relevance
“…Individual differences in latencies to shift attention during infancy appear to be concurrently associated with the ability to regulate emotion. An initial finding that 4-month-olds better able to disengage during Overlap trials were less susceptible to distress and more easily soothed (Johnson et al 1991b) was not replicated in two cohorts of similar-aged infants (Holmboe 2008, McConnell & Bryson 2005. However, saccadic reaction times in the Gap (and to a lesser extent the Overlap) conditions were positively associated with parentreported fear amongst 4-month-olds (Holmboe 2008, McConnell & Bryson 2005.…”
Section: Gap/overlap Task Performance and Concurrent Emotion Regulationmentioning
confidence: 93%
See 1 more Smart Citation
“…Individual differences in latencies to shift attention during infancy appear to be concurrently associated with the ability to regulate emotion. An initial finding that 4-month-olds better able to disengage during Overlap trials were less susceptible to distress and more easily soothed (Johnson et al 1991b) was not replicated in two cohorts of similar-aged infants (Holmboe 2008, McConnell & Bryson 2005. However, saccadic reaction times in the Gap (and to a lesser extent the Overlap) conditions were positively associated with parentreported fear amongst 4-month-olds (Holmboe 2008, McConnell & Bryson 2005.…”
Section: Gap/overlap Task Performance and Concurrent Emotion Regulationmentioning
confidence: 93%
“…An initial finding that 4-month-olds better able to disengage during Overlap trials were less susceptible to distress and more easily soothed (Johnson et al 1991b) was not replicated in two cohorts of similar-aged infants (Holmboe 2008, McConnell & Bryson 2005. However, saccadic reaction times in the Gap (and to a lesser extent the Overlap) conditions were positively associated with parentreported fear amongst 4-month-olds (Holmboe 2008, McConnell & Bryson 2005. Longer latencies to disengage during Overlap trials at 6 months of age have been associated with greater parent-reported distress and less smiling (McConnell & Bryson 2005) and with less soothability (Nakagawa & Sukigara 2019).…”
Section: Gap/overlap Task Performance and Concurrent Emotion Regulationmentioning
confidence: 98%
“…Children in the toddler study were a subset of a larger group of 48 infants, which was assessed monthly from 5 to 12 months of age. During the infant (5 to 12 month) phase, the study focused on two visual inhibitory control tasks: the looking A-not-B and Freeze-Frame tasks [ 55 , 56 ] (these data are the topic of separate manuscripts). At the completion of the 12-month visit, families were invited to continue participation by also becoming part of the toddler study.…”
Section: Studymentioning
confidence: 99%
“…One important form of inhibitory control is response inhibition; the ability to inhibit a prepotent or well-learned response which is often motoric in nature (Friedman & Miyake, 2004). Whilst response inhibition abilities are immature during infancy, it is possible to reliably measure early forms of response inhibition from the second half of the first year of life (Hendry et al, 2021;Holmboe et al, 2008Holmboe et al, , 2018Holmboe et al, , 2020. However, very little is known about the brain mechanisms supporting response inhibition in infancy and toddlerhood.…”
mentioning
confidence: 99%